1994
DOI: 10.1017/s0950268800051591
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of Akabane virus in the Middle East

Abstract: Serological evidence was used to confirm an outbreak of Akabane disease in cattle in the Turkish Province of Aydin in 1980. Thereafter, serum collections from the Middle East were screened for the presence of neutralizing antibodies to Akabane virus. The results indicate that the virus was present in a number of provinces on the south Turkish coast in 1979 and 1980 but that it probably did not persist into 1981; the virus had also been present on Cyprus in 1980 and on at least one previous occasion. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…Interestingly, the fact that this virus failed to persist in southern Turkey for more than two years indicates that the Middle East may be open to epidemic rather than endemic infection. The presence of neutralizing antibodies in the eastern Turkish Provinces of Gaziantep and Diyarbakir suggests that this might be the route whereby Akabane virus and probably other Simbu group viruses could invade the Middle East region (Taylor and Mellor, 1994). Regarding the infection by SBV, its associated disease appears in the adult cattle by a fall of the dairy production, fever, diarrhea being able to be severe and sometimes abortions.…”
Section: Schmallenberg Virus (Sbv) Was Identified Inmentioning
confidence: 99%
“…Interestingly, the fact that this virus failed to persist in southern Turkey for more than two years indicates that the Middle East may be open to epidemic rather than endemic infection. The presence of neutralizing antibodies in the eastern Turkish Provinces of Gaziantep and Diyarbakir suggests that this might be the route whereby Akabane virus and probably other Simbu group viruses could invade the Middle East region (Taylor and Mellor, 1994). Regarding the infection by SBV, its associated disease appears in the adult cattle by a fall of the dairy production, fever, diarrhea being able to be severe and sometimes abortions.…”
Section: Schmallenberg Virus (Sbv) Was Identified Inmentioning
confidence: 99%
“…Akabane virus has been reported in cattle in Turkey (Taylor and Mellor, 1994). Based on serological evidence, authors conclude that the virus was present in some areas of the south Turkish coast in 1979 and 1980 but that it probably did not persist into 1981.…”
Section: Introductionmentioning
confidence: 96%
“…Based on serological evidence, authors conclude that the virus was present in some areas of the south Turkish coast in 1979 and 1980 but that it probably did not persist into 1981. According to Taylor and Mellor (1994), the failure of Akabane virus to persist in southern Turkey for more than two years indicated that this area was open to epidemic rather than endemic infection. Neutralizing antibodies of Akabane virus were detected in serum samples of sheep, goats and cattle from Cyprus from 1970 onwards (Sellers and Herniman, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,8 Outbreaks of the disease have been reported in Japan, Australia, and Israel, and the antibodies to AKAV with or without virus isolation have been detected in domestic and wild ruminants in the continents of Africa, Asia, and Oceania. 5,[9][10][11] Diagnosis of the disease and surveillance of virus epidemics are based on the detection of virus-specific antibodies. A 7 and hemagglutination inhibition (HI) test 2 have been developed and used for this purpose.…”
mentioning
confidence: 99%